Encyclopedia of human services and diversity - Cousins, Linwood H., 1955- (Thousand Oaks, California : SAGE Publications, 2014)
Encyclopedia of Human Services and Diversity is the first encyclopedia to reflect the changes in the mission of human services professionals as they face today's increasingly diverse service population. It provides human services students, professors, librarians, and practitioners the reference information they need to meet the needs of an increasingly diverse population.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 22, 2014).
Keywords: Social service -- United States; Social work with minorities -- United States